Al-Qabisiâs Thoughts about Curriculum in Islamic Education - Daud, Al-Husaini M (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: This research is a literary study discussing the thoughts of an Islamic scientist from Tunisia, named Abu al-Hasan Ali bin Muhammad Khalaf al-Muâafiri al-Qabisi, 935-1014 AD (Anno Domini) / 324-403 AH (Anno Hijriah) about curriculum in the Islamic education. The objective of this research is to discuss some basic thoughts of education that had ever been used in the classic era, especially about curriculum. The result of this research are hoped to be positive inputs for educational organizer lately. All studies of this research were discussed with historical method; those were the efforts to reconstruct the past time of the study object. Meanwhile, in collecting the data, the researcher used the library research to explore and study the relevant resources, books and any supporting writings. The results that the researcher found from the book mentioned above were that the orientation of curriculum created by Al-Qabisi was applied through the lessons that had to be mastered by students, those included obligatory and optional lessons. The obligatory one consisted of Al-Qurâan and âAl-Hadistâ (words and deeds of the Prophet Muhammad), âfiqhâ (Islamic law pertaining to ritual obligation), moral, and Arabic writing, spelling, and reading. The optionals one were that the intensification of Arabic and its procedures/grammars (ânahwuâ, âsharafâ, âsyairâ, and rhetoric), arithmetic, and history.KEY WORDS: Education thought, curriculum, Al-Qabisi, Al-Qurâan and âAl-Hadistâ, Islamic education, young generation, and good character.Â About the Author: Al-Husaini M. Daud, M.A. is a Lecturer at the Department of Islamic Education History, Faculty of Tarbiyah (Education), Islamic College of Malikussaleh Lhokseumawe, Jalan Cempaka No.1 Lancang Garam, Banda Sakti, Lhokseumawe, Aceh Darussalam, Indonesia. E-mail address: beck_roprophai@yahoo.comHow to cite this article? Daud, Al-Husaini M. (2014). âAl-Qabisiâs Thoughts about Curriculum in Islamic Educationâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.187-196. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 2, 2014); Revised (March 4, 2014); and Published (April 28, 2014).